Miss me when I'm gone [large type] - Arsenault, Emily (Thorndike Press large print core, 2012)
Gretchen Waters is most famous for her memoir Tammyland, a "honky-tonk Eat, Pray, Love" about her divorce and her admiration for Tammy Wynette, Loretta Lynn, and Dolly Parton. When Gretchen dies falling on the stone steps outside of a library, everyone thinks it was an accident or a botched mugging. Jamie, Gretchen's best friend from college, certainly has no reason to suspect foul play. That is, until she becomes Gretchen's literary executor. From beyond the grave, Gretchen opens up a sinister new world through her writing . . .